Savoirs conquis, savoirs transmis - Bernard Schlemmer (Les éditions de la Maison des sciences de l'Homme, 2009)
This article compares the mode of knowledge transmission in traditional Moroccan craftsmanship with that used by the school - including in Morocco. The first part describes, - starting with the particular situation of the "Cooperative des potiers de Fez" (singular in its legal status although completely coherent with the traditional way of learning)- the characteristics of knowledge transmission. The second section faces the question of the transmission and retention of knowledge practices ; it examines the issue of economic imperatives faced by employers and teachers and the difficulties in teaching their skills. Then it shows how complex this situations can be and finally makes a link between this mode of knowledge transmission an the way religious knowledge is taught : in the relationship between spiritual guide and the neophyte. In conclusion, it will compare the two logics at work in each model.